2017
DOI: 10.1021/acs.est.5b04758
|View full text |Cite
|
Sign up to set email alerts
|

A Field Trial of TCE Phytoremediation by Genetically Modified Poplars Expressing Cytochrome P450 2E1

Abstract: A controlled field study was performed to evaluate the effectiveness of transgenic poplars for phytoremediation. Three hydraulically contained test beds were planted with 12 transgenic poplars, 12 wild type (WT) poplars, or left unplanted, and dosed with equivalent concentrations of trichloroethylene (TCE). Removal of TCE was enhanced in the transgenic tree bed, but not to the extent of the enhanced removal observed in laboratory studies. Total chlorinated ethene removal was 87% in the CYP2E1 bed, 85% in the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 48 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…For example, 4‐year‐old trees of ‘OP‐367’ were associated with a 99% reduction of chlorinated ethenes in PCE‐contaminated soils (James et al, ). In contrast, Legault et al () reported a reduced level of TCE removal from field‐soils relative to the quantities exhibited in the greenhouse, though transgenic poplars were associated with greater levels of TCE removal than their wild‐type counterparts. To increase TCE removal in the field, Doty et al () inoculated poplar trees with a natural bacterial endophyte, Enterobacter sp.…”
Section: Review Of Ecosystem Services At Phytoremediation Installationsmentioning
confidence: 90%
“…For example, 4‐year‐old trees of ‘OP‐367’ were associated with a 99% reduction of chlorinated ethenes in PCE‐contaminated soils (James et al, ). In contrast, Legault et al () reported a reduced level of TCE removal from field‐soils relative to the quantities exhibited in the greenhouse, though transgenic poplars were associated with greater levels of TCE removal than their wild‐type counterparts. To increase TCE removal in the field, Doty et al () inoculated poplar trees with a natural bacterial endophyte, Enterobacter sp.…”
Section: Review Of Ecosystem Services At Phytoremediation Installationsmentioning
confidence: 90%
“…In the past decade, the CYP2E1 gene has been introduced into various plants, including tobacco, poplar, Sesbania grandiflora, and Arabidopsis thaliana plants, for phytoremediation of different contaminations, including TCE (Doty et al, 2000;Doty et al, 2007;James et al, 2008;Legault et al, 2017), and DDT (Mouhamad et al, 2012).…”
Section: Mammalian Genes Transformed To Alfalfa For Phytoremediationmentioning
confidence: 99%
“…Natural treatment systems, such as constructed wetlands (Kassenga, Pardue, Blair, & Ferraro, ) phytoremediation (Legault et al, ), and in situ bioreactors (Gamlin, Cox, & Castor, ) using locally available materials, and the progress in understanding microbiology hold great promise for contaminated site remediation. Natural treatment systems leverage the power of nature and decrease emphasis on intensive engineered elements.…”
Section: Sustainable Remediation In the Next 10 Yearsmentioning
confidence: 99%